SAT0707-HPR PATIENT AND CLINICIAN PERSPECTIVES USED FOR SURVEY DEVELOPMENT TO INVESTIGATE THE NATURE, EXTENT AND IMPACT OF FOOT PROBLEMS IN PEOPLE WITH PSORIATIC ARTHRITIS. (June 2019) - Carter, Kate; Walmsley, Steven; Rome, Keith; Turner, Deborah E.
Abstract : Background: Despite recognition that hallmark features of psoriatic arthritis (PsA), such as enthesitis, are predominant and persistent in the foot and ankle [1], limited research has focused on the foot. Few published studies have used RA-specific outcome measures unlikely to capture the dermatological impact in PsA and there has been little incorporation of the patient perspective [1]. The importance of patient and clinician involvement as a central component of research design has been identified in PsA [2, 3], and provides a basis for defining what should be measured to represent comprehensively the experience of people with PsA-related foot problems and important domains of impact. Objectives: To develop a survey based on the views of people with PsA and clinicians on foot problems, their impact and the foot care needs. Methods: Interviews of people with PsA-related foot problems and focus groups with clinicians on their understanding of the patient experience were undertaken in Sydney, Australia and Auckland, New Zealand. A representative sample from public and private sector, from lower and higher socioeconomic geographical areas, as well as clinicians with different professional backgrounds was sought. Based on the themes from the qualitative interviews, previous research [1, 3] and clinical experience, survey items were generated by the research team using a consensus based approach. The survey was pre-tested using a 4-stage method that comprised; cognitive de-briefing of people with PsA, expert review panels of subject and survey design experts, cultural sensitivity assessment and pilot testing. All focus groups and interviews were audio-record, transcribed verbatim and survey items were revised based on comments made. Results: The final 60-item self-administered survey was developed based on feedback from each of the 4-stages, which related to wording, comprehension, timescales, content, repetition, number of survey items and overall survey design. Key survey domains included demographic (10%) and socioeconomic data (10%), global disease information (18%), foot and ankle characteristics (18%), and the impact of foot problems on daily life including daily routine, footwear choice, family life, work and accessing health care (44%). Percentage coverage of items directly reflects the dominant concerns of people with PsA-related foot problems and clinicians. Whilst priorities for clinicians included the diverse expression of disease and determining the nature of foot symptoms as mechanical or inflammatory, a key theme from patients was the psychological impact of foot involvement on daily life coupled with self-management strategies (coping skills, self-care activities and availability of social support), which was poorly recognised by clinicians. Consequently, nearly a quarter of survey content was dedicated to these areas of impact highlight by patients (23%). Engaging patients and clinicians in the survey development methods ensured that face and content validity were confirmed and cognitive and usability standards were achieved. Conclusion: By incorporating the views of those with the disease and of clinicians into the survey development process, good conceptual coverage of items important to both patients and clinicians was achieved whilst minimising responder burden. This is the first study to develop a survey on foot involvement in PsA based on best practice methods in qualitative survey design, which may have utility in the future development of assessment or screening tools. References: [1] Hyslop E, et al. Ann Rheum Dis. 2010;69:928. [2] Carter K, et al. Clin Rheumatol. 2019;8:1-9. [3] Orbai AM, et al. Ann Rheum Dis. 2016;76:673-680. Disclosure of Interests: None declared